Strategi Internalisasi Nilai-Nilai Karakter Religius Melalui Mata Kuliah Akidah Akhlak - Maulida, Ghina Rahmah; Ratnasari, Dwi (Tadarus Tarbawy : Jurnal Kajian Islam dan Pendidikan, 2024)
In this era of globalization and technological progress which is full of moral challenges, Aqidah Akhlak courses on campus are an important strategy for internalizing religious character values in students. Amidst the influence of instant culture and pragmatism, this religious education not only forms a spiritual foundation, but also strengthens the integrity and morality of the younger generation, making them ready to face the dynamics of modern life and compete positively in society. This research aims to provide a description of the strategy for internalizing religious character values through the Aqidah Akhlak course, including understanding, applying and living it, in order to form individuals with integrity and religious character at various levels of education, especially at UIN Sunan Kalijaga Yogyakarta. This research uses a qualitative method with a descriptive approach and case study method. Data was obtained using observation methods, in-depth interviews, and document analysis, then analyzed using the Miles, Huberman, and Saldana interactive model which includes data reduction, data presentation, and then drawing conclusions. Research findings indicate that the strategy for internalizing religious character values through the Aqidah Akhlak course in higher education uses methods of modeling behavior, forming habits, applying rules, and providing motivation. This strategy forms students who are sincere, honest, disciplined, patient, and care about others, and are able to integrate religious values in academic and social life. The implications of this research emphasize the importance of a holistic approach in courses to build student character who is competitive and has integrity in the modern education era.Keywords: Internalization, Religious Character, Moral Creed